Composite Index for Assessment of Sanitation and Environmental Health in Municipalities of the Baixo Pardo/Grande Watershed - Shibasaki, Karina; Ventura, Katia Sakihama; Rezende, Danilo (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2023)
The management of services for environmental health can be achieved through the use of indicators as a practice to improve urban infrastructure. The goal was to analyze the sanitary and environmental conditions in 14 municipalities in the Baixo Pardo/Grande watershed. The following steps were carried out: i) identification of indicators, ii) structuring of an evaluation model on a scale from 0 (zero) to 100, iii) consultation with specialists using the Analytic Hierarchy Process (AHP) method, iv) elaboration of the index in georeferenced maps in QGIS, version 3.22. The model generated 18 sub-indicators grouped into 7 indicators. The index ranged from 21.55 to 66.72%, with 8 municipalities deemed medium health level, 5 deemed low and 1 unhealthy. In most municipalities, solid waste indicators stood out with high condition, while vegetation cover and urban drainage reached the lowest values. It is essential to establish measures and public policies to guarantee the evolution of these indicators in the basin.